Cognitive, motor, behavioural and academic performances of children born preterm: a meta‐analysis and systematic review involving 64 061 children. (11th October 2017) - Allotey, J; Zamora, J; Cheong‐See, F; Kalidindi, M; Arroyo‐Manzano, D; Asztalos, E; van der Post, JAM; Mol, BW; Moore, D; Birtles, D; Khan, KS; Thangaratinam, S
Abstract : Background: Preterm birth may leave the brain vulnerable to dysfunction. Knowledge of future neurodevelopmental delay in children born with various degrees of prematurity is needed to inform practice and policy. Objective: To quantify the long‐term cognitive, motor, behavioural and academic performance of children born with different degrees of prematurity compared with term‐born children. Search strategy: PubMed and Embase were searched from January 1980 to December 2016 without language restrictions. Selection criteria: Observational studies that reported neurodevelopmental outcomes from 2 years of age in children born preterm compared with a term‐born cohort. Data collection and analysis: We pooled individual estimates of standardised mean differences (SMD) and odds ratios (OR) with 95% confidence intervals using a random effects model. Main results: We included 74 studies (64 061 children). Preterm children had lower cognitive scores for FSIQ (SMD: −0.70; 95% CI: −0.73 to −0.66), PIQ (SMD: −0.67; 95% CI: −0.73 to −0.60) and VIQ (SMD: −0.53; 95% CI: −0.60 to −0.47). Lower scores for preterm children in motor skills, behaviour, reading, mathematics and spelling were observed at primary school age, and this persisted to secondary school age, except for mathematics. Gestational age at birth accounted for 38–48% of the observed IQ variance. ADHD was diagnosed twice as often in preterm children (OR: 1.6; 95% CI: 1.3–1.8), with a differential effect observed according to the severity of prematurity ( I 2 = 49.4%, P = 0.03). Conclusions: Prematurity of any degree affects the cognitive performance of children born preterm. The poor neurodevelopment persists at various ages of follow up. Parents, educators, healthcare professionals and policy makers need to take into account the additional academic, emotional and behavioural needs of these children. Tweetable abstract: Adverse effect of preterm birth on a child's neurodevelopment persists up to adulthood. Tweetable abstract: Adverse effect of preterm birth on a child's neurodevelopment persists up to adulthood.